2022
DOI: 10.1177/08850666221082540
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone for Pediatric Critical Asthma: A Multicenter Descriptive Study

Abstract: Background Systemic corticosteroids are vital to critical asthma management. While intravenous methylprednisolone is routinely used in the pediatric intensive care unit (PICU) setting, recent data supports dexamethasone as an alternative. Using the Pediatric Health Information System (PHIS) registry, we assessed trends and variation in corticosteroid prescribing among children hospitalized for critical asthma. Methods We performed a multicenter retrospective cohort study using PHIS data among children 3-17 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 42 publications
(55 reference statements)
0
7
0
Order By: Relevance
“…Although prior survey data of United States pediatric intensivist respondents suggested a preference for IV methylprednisolone in cases of critical asthma, 14 wide variation in practice has been reported including a multicenter, registry‐based cohort study by Sellers et al who queried an administrative data set, the Pediatric Health Information System registry 15 . In their report including ~27,000 pediatric critical asthma encounters from 49 children's hospitals, dexamethasone‐only prescribing rates in the PICU exhibited a linear increase of 0.5% per year from 0.6% in 2011 to 4.5% in 2019.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although prior survey data of United States pediatric intensivist respondents suggested a preference for IV methylprednisolone in cases of critical asthma, 14 wide variation in practice has been reported including a multicenter, registry‐based cohort study by Sellers et al who queried an administrative data set, the Pediatric Health Information System registry 15 . In their report including ~27,000 pediatric critical asthma encounters from 49 children's hospitals, dexamethasone‐only prescribing rates in the PICU exhibited a linear increase of 0.5% per year from 0.6% in 2011 to 4.5% in 2019.…”
Section: Discussionmentioning
confidence: 99%
“…Health Information System registry. 15 In their report including ~27,000 pediatric critical asthma encounters from 49 children's hospitals, dexamethasone-only prescribing rates in the PICU exhibited a linear increase of 0.5% per year from 0.6% in 2011 to 4.5% advantage for dexamethasone over methylprednisolone, prednisone, and prednisolone. Observational cohort data suggest two daily doses of dexamethasone may be equivalent to a 5-day course of prednisone or methylprednisolone.…”
Section: Sellers Et Al Who Queried An Administrative Data Set the Ped...mentioning
confidence: 99%
See 2 more Smart Citations
“…It is an observational study using a large, administrative database. Although the possibility for data entry and processing errors exists, data that are stored in the PHIS database undergo several quality checks before assimilation into the database and it has supported several studies of pediatric asthma (6, 35, 36). This study is observational in nature and subject to several potential biases, and any observed relationships are only associations, not causal.…”
Section: Discussionmentioning
confidence: 99%